The Influence of Sporting Events on the Development of Urban Tourism - the Example of Tennis Tournaments - Piechota , Natalia (Studia Oeconomica Posnaniensia, 2014)
The aim of this paper is to identify the impact of sporting events on tourist flows in hosting cities based on the example of tennis tournaments. A statistical analysis was conducted which included data from the years 2000-2010 relating to attendance at six different tennis events along with the monthly number of visitors to the hosting destinations. The findings show that the strength of the correlation between these two factors depends on the importance of the tournament and the characteristics of the city. The results obtained were used to analyse the position of the Poznań Open (formerly Porsche Open) tournament.